“Llop Mougn” Film Animasi 2D Dengan Teknik Rotoscope - Oktivani Anggia Rahmalita; Mahendradewa Suminto (Institut Seni Indonesia Yogyakarta, 2018)
Bedwetting habits are things that must have been experienced by everyone, especially young children, and various methods were taken to stop this. The lack of knowledge of some people in the past will be something that believes in myth. The myth of biting the navel by dragonflies is believed to stop the bedwetting habit. This is what then based on personal experience raises the idea of creating animated films because they are interesting and unique. added by using a combination storyline. Unify real events with dreams.The animated short film